The Clergy Occupational Distress Index (CODI): Background and Findings from Two Samples of Clergy - Frenk, Steven M. (Journal of religion and health, 2013)
This study demonstrates the reliability and validity of the Clergy Occupational Distress Index (CODI). The five-item index allows researchers to measure the frequency that clergy, who traditionally have not been the subject of occupational health studies, experience occupational distress. We assess the reliability and validity of the index using two samples of clergy: a nationally representative sample of clergy and a sample of clergy from nine Protestant denominations. Exploratory factor analysis and Cronbach's scores are generated. Construct validity is measured by examining the association between CODI scores and depressive symptoms while controlling for demographic, ministerial, and health variables. In both samples, the five items of the CODI load onto a single factor and the Cronbach's alpha scores are robust. The regression model indicates that a high score on the CODI (i.e., more frequent occupational distress) is positively associated with having depressive symptoms within the last 4 weeks. The CODI can be used to identify clergy who frequently experience occupational distress and to understand how occupational distress affects clergy's health, ministerial career, and the functioning of their congregation.